Shelf Life and Acceptance of Aloe Vera Gel (AVG) Chicken Nuggets as an Alternative Food for School Children - Yuska, Defniwita; Afriza, Renita; Hasniyati, Rina (Sarana Ilmu Indonesia (salnesia), 2024)
Aloe vera gel (AVG) chicken nuggets are an alternative food that is very suitable for consumption by school-aged children. These foods contain protein and antioxidants. So that what is consumed is safe and of good quality, it is necessary to measure its shelf life using the total plate count (TPC) parameters and consumer acceptance of the product. This type of research is quasi-experimental for testing shelf life and pre-experimental for testing the acceptability of chicken nuggets among schoolchildren. The shelf life estimation method is ASLT (Accelerated Shelf Life Test). This research was carried out at the Padang Food Ingredient and Baristand Science Laboratory from May to October 2022. Acceptability tests were carried out at the domicile of the selected samples. The parameter used in storing AVG chicken nuggets is ALT. Data analysis was carried out on acceptability using the Wilcoxon test. The research results showed that the storage temperature with the longest shelf life was -200 °C, with a shelf life of 26,65 weeks. The average acceptance of the product by schoolchildren is 99,5%. This research concluded that the lower the temperature, the longer the shelf life of AVG chicken nuggets. School-age children well receive AVG chicken nuggets. Suggestions for storing ground and frozen meat products pay attention to temperature because temperature greatly influences the amount of TPC contamination.